Observations on Rotating Instabilities and Spike Type Stall Inception in a High-Speed Multistage Compressor. (28th August 2017) - Schreiber, Johannes; Paoletti, Benoit; Ottavy, Xavier
Abstract : This work investigates high-frequency measurements for the contribution to the understanding of different stall inception types in high-speed multistage compressors. A 3.5-stage high-speed axial multistage compressor is investigated with a 2 MW test rig in the Laboratoire de Mécanique des Fluides et d'Acoustique (LMFA) at Ecole Centrale de Lyon, France. Two different types of instabilities arise in this compressor as a function of shaft speed. At part speed, a controversy called "rotating instability" type flow field modulation is identified with the measurements. New results are the demonstration of the periodic behavior of this instability and the analogy to classical frequency modulation, periodic to one revolution of the instability. Furthermore, the amplitude of the instability is modulated by the time period of a rotor revolution. At nominal speed, the abrupt spike type stall inception is detected, taking usually less than five rotor revolutions.